Attention in a social world - Posner, Michael I. (Oxford ; New York : Oxford University Press, 2012)
This volume summarizes the research on the brain mechanisms of attention, especially those from human imaging studies. Michael Posner places this research in the context of human development educational applications, and brain pathology.
Includes bibliographical references and indexes.
Description based on print version record.
Keywords: Attention